Removal of Dicofol from Waste-Water Using Advanced Oxidation Process. (2016) - Mohammed, Sibhi; Fasnabi, P.A.
Abstract: Water is perhaps our most valuable resource and thus should be recycled. Many of the current waste water treatment only concentrate on the pollutant without degrading it or eliminating it. In this sense, Advanced Oxidation Processes (AOP) are possibly one of the most effective methods for the treatment of wastewater containing organic products. It uses different methods to produce hydroxyl radicals which are responsible for oxidation of pollutants. This work deals with the study on Fenton process and UV/ H2 O2 process for the removal of dicofol present in waste water. Dicofol is an organochlorine pesticide which is structurally similar to DDT and used extensively in a wide variety of crops. The effects of pH, H2 O2 concentration and Fe 2+ concentration for AOP processes are studied for water sample containing dicofol. Kinetic studies were conducted for Fenton, UV/H2 O2 and H2 O2 processes at the optimized conditions, which show the applicability of first order kinetics.